2023
DOI: 10.1002/jdn.10308
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of cognitive impairments in the valproic acid‐induced animal model of autism in BALB/c mice infected with Toxoplasma gondii

Saeed Sheikhshoaee,
Farahnaz Taheri,
Khadijeh Esmaeilpour
et al.

Abstract: PurposeToxoplasmosis is a disease caused by infection with a type of coccidial protozoan parasite called Toxoplasma gondii. The relationship between toxoplasmosis and cognitive disorders in neurodegenerative diseases has been proven. There is also evidence that children born to Toxoplasma‐infected mothers are more likely to develop autism.MethodsIn the present study, Toxoplasma‐infected pregnant BALB/c mice were given valproic acid to induce autism in their male offspring, and their social behaviors, learning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…An in vivo study evaluating the intrauterine exposure of mice to 0.4% of valproic acid identified alterations in social interaction and cognitive functions, hypersensitivity to heat and pain stimuli in offspring exposed during gestation, behaviors characteristic of ASD [ 77 ]. In this context, several studies have used the animal model of autism induced by valproic acid to study changes related to ASD, with the administration of VPA ranging from 500/600 mg/kg [ 78 , 79 , 80 ].…”
Section: The Influence Of Environmental Hazardsmentioning
confidence: 99%
“…An in vivo study evaluating the intrauterine exposure of mice to 0.4% of valproic acid identified alterations in social interaction and cognitive functions, hypersensitivity to heat and pain stimuli in offspring exposed during gestation, behaviors characteristic of ASD [ 77 ]. In this context, several studies have used the animal model of autism induced by valproic acid to study changes related to ASD, with the administration of VPA ranging from 500/600 mg/kg [ 78 , 79 , 80 ].…”
Section: The Influence Of Environmental Hazardsmentioning
confidence: 99%
“…Some studies suggested that LT may indirectly resulted to higher risk perception [77,78], impaired decision-making [34,68], lower novelty seeking [79,80], higher occurrence of intermittent explosive disorder (rage) [32], lower intelligence quotients (IQ), mental retardation, epilepsy, headache and migraine [2,30,51], and childhood autism in humans [81] and aggravating the cognitive impairments including social communication, recognition memory and avoidance memory in an animal model of autism [82].…”
Section: Behavioural and Personality Traitsmentioning
confidence: 99%